Developing a mediation relationship model of service quality, basic artificial intelligent and behavioural intention constructs in the use of artificial intelligent security technology in UAE - Alafreet Alkuwaiti, Salem Ahmed Abdulla (2023)
The goal of this research was to create and test a moderating model which fundamental artificial intelligence (AI) serve as a moderator in the link between service quality and behavioral intention to employ AI security technology in the United Arab Emirates. The study is that it focuses on improving service quality in the field of AI security in the UAE. The performance expectation, effort, and quality domains each include four groupings of elements. Expectancy, social influence, and a favorable situation were uncovered throughout the literature study and were utilized as the core components of the questionnaire. In this study, quantitative methods were used. 420 questionnaires were distributed, of which 389 (92.6%) were returned and completed. 377 feedback were deemed usable and legitimate for further data analysis as recommended by the sample size of the study. The data was then descriptively analyzed using SPSS before being inferentially analyzed with Smart-PLS. The study's findings also confirmed that basic artificial intelligence has a partial mediation impact on the relationship between service quality and behavioral intention when it comes to the use of Al security technology. There is significant indirect effect of service quality between artificial intelligence and intention to use artificial intelligence as indicated by coefficient of 0.245, t-value of 0.055 and p-value 0.000. This shows that service quality mediates the relationship between artificial intelligence and intention to use artificial intelligence. Similarly, the transactional artificial intelligence path leading to intention to use artificial intelligence security through service quality is significant. This is indicated by coefficient of 0.043, t-value of 3.107, and p-value of 0.002 significant at 0.01 significance level and it may be concluded that service quality increases the intention to use AI security technologies because the support of AI security technologies. Job performance and the ease of using such technologies make people aware of the perceived usefulness of such technologies, which also influence others to use such technologies. Also, the need of the users to AI security technologies increases the use of AI security technologies since such technologies improve job performance, which makes users satisfied and interested in similar future technologies